2010
DOI: 10.1016/j.plefa.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Cide-a and Cide-c are induced in the progression of hepatic steatosis and inhibited by eicosapentaenoic acid

Abstract: Cide-a and Cide-c belong to the cell death-inducing DNA fragmentation factor-alpha-like effector family. Recent evidences suggest that these proteins may be involved in lipid accumulation in liver and adipose tissues. We confirmed that in the high-fat/high-sucrose diet-induced murine model of hepatic steatosis, the expression levels of the Cide-a and Cide-c genes were markedly and time-dependently increased, but returned to normal levels following improvement of hepatic steatosis by eicosapentaenoic acid (EPA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…Numerous lines of evidence are now emerging that suggest a role for LD proteins in the progression of NAFLD to nonalcoholic steatohepatitis (NASH). Several studies have identified proteins known to antagonize lipolysis including PLIN1, PLIN2, and CIDEC to be increased in NASH . Liver‐specific ablation of comparative gene identification‐58 leads to NASH and fibrosis through a reduction in hydrolytic activity .…”
Section: Dysregulation Of Lds and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Numerous lines of evidence are now emerging that suggest a role for LD proteins in the progression of NAFLD to nonalcoholic steatohepatitis (NASH). Several studies have identified proteins known to antagonize lipolysis including PLIN1, PLIN2, and CIDEC to be increased in NASH . Liver‐specific ablation of comparative gene identification‐58 leads to NASH and fibrosis through a reduction in hydrolytic activity .…”
Section: Dysregulation Of Lds and Diseasementioning
confidence: 99%
“…Several studies have identified proteins known to antagonize lipolysis including PLIN1, PLIN2, and CIDEC to be increased in NASH. [28][29][30] Liver-specific ablation of comparative gene identification-58 leads to NASH and fibrosis through a reduction in hydrolytic activity. 31 Additionally, the PNPLA3 variant, which has been linked to decreased lipolysis, promotes the progression of NAFLD to NASH.…”
Section: Dysregulation Of Lds and Diseasementioning
confidence: 99%
“…102,103 This function however is not restricted to adipocytes, and both proteins are also significantly upregulated in steatotic livers where they are thought to induce hepatic TG accumulation. 37,104,105 A human mutation in Fsp27 resulting in the expression of a truncated protein has been reported to cause partial lipodystrophy and insulin-resistant diabetes in the afflicted individual. 106 It has been shown that Fsp27 enhances LD clustering and then fusion 107 by mediating the transfer of TG from smaller to larger LDs at LD contact sites (LDCS) where the proteins are highly enriched.…”
Section: Lipid Droplet Growth: Expansion and Fusionmentioning
confidence: 99%
“…Two critical cell cycle regulators, CyclinD1 (Ccnd1) and cyclin-dependent kinase inhibitor 1A (Cdkn1a) in Network 1, are also associated with innate immune system activation and were increased in a time-dependent manner in high-fat diet-fed mice. Genes in Network 2 were related to lipolysis, lipid uptake and lipid transport, and interestingly involved in liver fibrosis, steatotic liver, and NAFLD (Shechter et al 2003;Lydatakis et al 2006;Guillén et al 2009;Jinno et al 2010;Yang et al 2010). Tnf, Cidea, Acox1, S100a11, Ly6d, Lpl, and Idh1 were up-regulated in a time-dependent manner compared to normal diet-control.…”
Section: Core Molecular Network Underlying the Development Of Diet-imentioning
confidence: 99%